Comparison of clinical safety and efficacy of dexmedetomidine, remifentanil, and propofol in patients who cannot tolerate non-invasive mechanical ventilation: A prospective, randomized, cohort study - Altınkaya Çavuş, Mine; Gökbulut Bektaş, Serife; Turan, Sema (Frontiers in Medicine, 2022)
ABSTRACT Background and objectives Noninvasive ventilation (NIV) is used in intensive care units (ICUs) to treat of respiratory failure. Sedation and analgesia are effective and safe for improving compliance in patients intolerant to NIV. Our study aimed to evaluate the effects of dexmedetomidine, remifentanil, and propofol on the clinical outcomes in NIV intolerant patients. Methods This prospective randomized cohort study was conducted in a tertiary ICU, between December 2018 and December 2019. We divided a total of 120 patients into five groups (DEXL, DEXH, REML, REMH, PRO). IBM SPSS Statistics 20 (IBM Corporation, Armonk, New York, USA) was used to conduct the statistical analyses. Results The DEXL, DEXH, REML, and REMH groups consisted of 23 patients each while the PRO group consisted of 28 patients. 75 patients (62.5%) became tolerant of NIV after starting the drugs. The NIV time, MV time, ICU LOS, hospital LOS, intubation rate, side effects, and mortality were significantly different among the five groups (P = 0.05). In the groups that were given dexmedetomidine (DEXL, and DEXH), NIV failure, mortality, ICU LOS, and hospital LOS were lower than in the other groups. Conclusion In this prospective study, we compared the results of three drugs (propofol, dexmedetomidine, and remifentanil) in patients with NIV intolerance. The use of sedation increased NIV success in patients with NIV intolerance. NIV failure, mortality, ICU LOS, MV time, and hospital LOS were found to be lower with dexmedetomidine.